3x+6-x=7+x-4

Simple and best practice solution for 3x+6-x=7+x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+6-x=7+x-4 equation:


Simplifying
3x + 6 + -1x = 7 + x + -4

Reorder the terms:
6 + 3x + -1x = 7 + x + -4

Combine like terms: 3x + -1x = 2x
6 + 2x = 7 + x + -4

Reorder the terms:
6 + 2x = 7 + -4 + x

Combine like terms: 7 + -4 = 3
6 + 2x = 3 + x

Solving
6 + 2x = 3 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + 2x + -1x = 3 + x + -1x

Combine like terms: 2x + -1x = 1x
6 + 1x = 3 + x + -1x

Combine like terms: x + -1x = 0
6 + 1x = 3 + 0
6 + 1x = 3

Add '-6' to each side of the equation.
6 + -6 + 1x = 3 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = 3 + -6
1x = 3 + -6

Combine like terms: 3 + -6 = -3
1x = -3

Divide each side by '1'.
x = -3

Simplifying
x = -3

See similar equations:

| 186.34x+24527=13.01x+108053 | | 8(1+5)+5=13+5x | | x/5+14=17 | | 127-6x=12x+21 | | 2(2n-1)=(8n+4)+1 | | x/2+1=12 | | 3X/(X^2-9)-2/(3X+9) | | x/3+5=14 | | 3(4x-2)+5=12x+8 | | 5a-20=3a+4.5 | | 9x+21=4x+4 | | -5600.00+200.00x=-2800 | | x/5+6=8 | | 4l-10=112 | | 7y+2(y-5)=4(y+2)-4 | | m-9=20 | | 9l-20=86 | | 20-9l=86 | | 3byx(-5yb)= | | 16=m-6 | | (2x+10)(x-12)= | | 2x+2*4=16 | | (3-2i)(x+iy)=2(x-2iy)+2i-1 | | 3x/5+44=12x/25+8 | | 2x-3*4=-4 | | -149-7x= | | 4w+10=96 | | 3x/8-9=13+x/8 | | y/5.4=7.2 | | 2t^2+4t+8=0 | | -2y+7=Y | | 96/10 |

Equations solver categories